Penggunaan Kopi Luwak Dalam Gastrodiplomasi Kopi Indonesia: Perspektif Sustainability dan Ethical Practices - Muhammad Sabilul Izzah (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes how Kopi Luwak is used as an instrument of Indonesian coffee gastrodiplomacy through the framework of Joseph S. Nye's soft power concept. According to Nye, the ability to influence international actors does not depend on coercion, but rather on organic appeal determined by three main sources: political values, foreign policy, and cultural appeal. Using qualitative descriptive methods, this study examines how Kopi Luwak acts as a medium that reflects national identity in diplomatic reception and serves as a foundation for Indonesia to build normative authority in the international coffee trading system. The results show that Kopi Luwak's exotic cultural appeal has succeeded in creating a global trend of premium coffee consumption based on the animal's natural fermentation, as evidenced by the phenomenon of replication of production methods by various competing countries. However, Kopi Luwak's long-term effectiveness as an instrument of soft power and a global norm-shaper is still limited to the provision of normative ecological standards and ethical practices at the field level, which serve as the basis for determining the credibility of Indonesia's diplomatic narrative on the international stage.
Finalisasi oleh Agus 15 Juli 2026
Keywords: Gastrodiplomasi; Sustainability; Ethical Practices; Soft Power; Kopi Luwak